2009
DOI: 10.1097/eja.0b013e32831bc665
|View full text |Cite
|
Sign up to set email alerts
|

Retention and transferability of team resource management skills in anaesthetic emergencies: the long-term impact of a high-fidelity simulation-based course

Abstract: Team resource management skills learnt in a single educational intervention, based on simulated anaesthetic emergencies, are retained over the long term, translated into clinical practice and are transferable across the breadth of clinical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Most research in the area of HFS and transfer of learning has focused on training anesthesia and medical students. Minimal research has been conducted in the discipline of nursing to validate whether students that complete HFS training are able to transfer knowledge and skills learned to the traditional clinical setting (Alinier, Hunt, Gordon, & Harwood, 2006;Kuduvalli, Parker, Leuwer, & Guha, 2009;Domuracki, Moule, Owen, Kostandoff, & Plummer, 2009). However, there are nursing programs that have chosen to replace traditional clinical training for HFS clinical experiences (Nehring, 2008).…”
Section: Hfs Researchmentioning
confidence: 99%
“…Most research in the area of HFS and transfer of learning has focused on training anesthesia and medical students. Minimal research has been conducted in the discipline of nursing to validate whether students that complete HFS training are able to transfer knowledge and skills learned to the traditional clinical setting (Alinier, Hunt, Gordon, & Harwood, 2006;Kuduvalli, Parker, Leuwer, & Guha, 2009;Domuracki, Moule, Owen, Kostandoff, & Plummer, 2009). However, there are nursing programs that have chosen to replace traditional clinical training for HFS clinical experiences (Nehring, 2008).…”
Section: Hfs Researchmentioning
confidence: 99%
“…La recomendación de reorfertar la sesión experimentada fue de 4,9/5 [38]. Si bien no lo experimentaron, citan otros estudios en donde se demuestra la transferencia de conocimiento a la realidad [39] [40], así como una mayor retención del conocimiento en comparación con estudiantes no expuestos a este tipo de experiencias [41]. Respecto a la autoevaluación.…”
Section: G Evidencia De Los Resultados De La Simulación Clínicaunclassified
“…Simulation has already been shown to be of value in improving communication skills and in communication with colleagues for anaesthetists attending a one day crisis management course [6]. Recent work at our centre [7] has also shown that team resource management skills (of which communication featured highly) were retained for up to 20 months following a one day course in crisis management. It will be interesting to see the impact that simulation has on future training in communication skills, particularly in light of the recent report from the Chief Medical Officer stating that simulation-based training needs to be valued and adequately resourced by NHS organisations [8].…”
Section: ó 2009 the Association Of Anaesthetists Of Great Britain Andmentioning
confidence: 98%